2010
DOI: 10.1158/1535-7163.mct-09-1169
|View full text |Cite
|
Sign up to set email alerts
|

IFNγ Restores Breast Cancer Sensitivity to Fulvestrant by Regulating STAT1, IFN Regulatory Factor 1, NF-κB, BCL2 Family Members, and Signaling to Caspase-Dependent Apoptosis

Abstract: Antiestrogens are effective therapies for the management of many estrogen receptor-α (ER)-positive breast cancers. Nonetheless, both de novo and acquired resistance occur and remain major problems in the clinical setting. IFNγ is an inflammatory cytokine that induces the expression and function of IFN regulatory factor 1 (IRF1), a tumor suppressor gene that can increase antiestrogen responsiveness. We show that IFNγ, but not IFNα, IFNβ, or fulvestrant (ICI; ICI 182,780; Faslodex), induces IRF1 expression in an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 52 publications
2
65
0
Order By: Relevance
“…[28][29][30][31][32] It is believed that STAT1 exerts its tumor suppressor effects by modulating the transcription of a host of proapoptotic and antiproliferative genes, 1,37 such as IRF-1, 23 caspases, 37,38 members of the death receptor family (iNOS, Fas/FasL) and tumor necrosis factor-related apoptosis ligand (TRAIL), [39][40][41][42] Bcl-xL, and Bcl-2. 43,44 Nonetheless, there is evidence suggesting that STAT1 may be oncogenic in specific experimental models and/or cell types, as highlighted in a recent review article. 4 For instance, it was found that STAT1-deficient mice are protected from developing leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31][32] It is believed that STAT1 exerts its tumor suppressor effects by modulating the transcription of a host of proapoptotic and antiproliferative genes, 1,37 such as IRF-1, 23 caspases, 37,38 members of the death receptor family (iNOS, Fas/FasL) and tumor necrosis factor-related apoptosis ligand (TRAIL), [39][40][41][42] Bcl-xL, and Bcl-2. 43,44 Nonetheless, there is evidence suggesting that STAT1 may be oncogenic in specific experimental models and/or cell types, as highlighted in a recent review article. 4 For instance, it was found that STAT1-deficient mice are protected from developing leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…61 The transcriptional activity of NF-kB p65 is further reduced when breast cancer cells are treated with both IFN-g and the steroidal antiestrogen fulvestrant ICI. 61 IRF-1 was also expressed in the spontaneously immortalized nonmalignant human breast cell line, MCF-10F, cultured with TNF-a, IFN-g, and the combination of TNF-a and IFN-g. In contrast to the human breast cancer cells, however, a change in the expression of NF-kB p65 in the nuclear fraction was not observed in this nonmalignant human breast cell line.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-Á has numerous effects on hematopoietic and tumor cells (19,30,31). One of the consequences of IFN-Á treatments is the induction of apoptosis (20,32). Moreover, Lester et al (33) showed that an ever greater augmentation of IFN-Á production could be caused by neutralization of IL-10 activity.…”
Section: Discussionmentioning
confidence: 99%